Risk Factors of Pilonidal Sinus in a Tertiary Care Hospital of Rawalpindi: A Descriptive Cross-sectional Study - Khan, Tayyab Mumtaz; Akram, Jehanzeb; Durrani, Muhammad Saoban Khan; Ur Rehman, Muhammad Hammad; Basharat, Mehak; Saeed, Momna; Shehzadi, Uns; Attiq, Aamna; ul Ain, Qurat; Shahid, Muhammad Usman (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: Pilonidal sinus incidence is increasing in surgical departments all over the world. Pilonidal sinus is under the influence of several factors. These factors are studied well in various parts of the world; however, these factors are understudied in Pakistan. This study aimed to find out the risk factors of pilonidal sinus among the patients diagnosed with pilonidal sinus. Methodology: This descriptive cross-sectional study was conducted among one hundred and eight patients with pilonidal sinus at Benazir Bhutto Hospital Rawalpindi, for one year from January 2021 to January 2022. Ethical approval and informed consent were obtained before the start of study. Patients' enrollment was done according to a developed inclusion and exclusion criteria. Convenient sampling technique was also applied for recruitment of participants. Data was collected through a self-designed questionnaire. Descriptive statistics were utilized for the data analysis. Data analysis was performed by SPSS version 25.0 (IBM Corp., Armonk, NY). Findings: Pilonidal sinus frequency was high among the patients who had age group of 11 to 30 years (68.52%), male gender (62.96%), driving profession (37.96%), family history of pilonidal sinus (64.82%), high body mass index(60.18%), daily sitting for more than 6 hours (79.62%), sitting on hard surfaces (63.88%), hairy skin (55.55%), excessive sweating (68.52%), poor hygiene of sacrococcygeal region (77.78%), number of baths less than three times per week (61.11%), and light colored skin (62.04%). Recommendations: This study recommends that health authorities should make people educated regarding the risk factors that lead to pilonidal sinus. The study also recommends that people should reduce their body weight, sit over soft places and should avoid continuous sitting for long periods. People should take care of hygiene, especially of sacrococcygeal regions by shaving hair, drying moisture, and taking frequent baths.